Canada, view of rocky shore in Nova Scotia at Cape Breton Highlands National Park - Forman, Harrison, 1904-1978 (1959)
Nova Scotia [Aug. 1959?] 'known for its spectacular highlands and ocean scenery. Steep cliffs and deep river canyons carve into a forested plateau bordering the Atlantic Ocean.' Cape Breton Highlands National Park of Canada. (2013). Parks Canada. Retrieved from http://www.pc.gc.ca/pn-np/ns/cbreton/index.aspx Grayscale Forman Safety Negatives, Box 22